The Gut Microbiota Determines the High-Altitude Adaptability of Tibetan Wild Asses (Equus kiang) in Qinghai-Tibet Plateau - Liu, Hongjin; Han, Xueping; Zhao, Na; Hu, Linyong; Wang, Xungang; Luo, Chongliang; Chen, Yongwei; Zhao, Xinquan; Xu, Shixiao (Frontiers in Microbiology, 2022)
It was acknowledged long ago that microorganisms have played critical roles in animal evolution. Tibetan wild asses (TWA, Equus kiang), as the only wild perissodactyls on the Qinghai-Tibet Plateau (QTP), the first national protected animals, however, knowledge about the relationships between their gut microbiota and host’s adaptability remains poorly understand. Herein, 16S rRNA and metagenomic sequencing approaches were employed to investigate the unique gut microbiota-host associations in TWA and compare them against those of the co-resident livestock of yak (Bos grunnies) and Tibetan sheep (Ovis aries). Results revealed that the gut microbiota of yak and Tibetan sheep underwent convergent evolution. By contrast, the intestinal microflora of TWA diverged in a direction enabling the host to subsist on sparse, low-quality forage. Meanwhile, high microbial diversity (Shannon and Chao1 indices), cellulolytic activity, and abundant indicator species such as Spirochaetes, Bacteroidetes, Prevotella_1, and Treponema_2 supported forage digestion and short-chain fatty acid production in the gut of TWA. Meanwhile, the enterotype identification analysis showed that TWA shifted their enterotype in response to low-quality forage to better utilize forage nitrogen and short fatty acid production. Metagenomic analysis revealed that plant biomass degradation microbial consortia, genes and enzymes like the cellulolytic strains (Prevotella ruminicola, Ruminococcus flavefaciens, Ruminococcus albus, Butyrivibrio fibrisolvens, and Ruminobacter amylophilus) as well as carbohydrate metabolism genes (GH43, GH3, GH31, GH5, and GH10) and enzymes (β-glucosidase, xylanase, and β-xylosidase etc.) had a significantly higher enrichment in TWA. Our results indicate that gut microbiota can improve the adaptability of TWA through plant biomass degradation and energy maintenance by the functions of gut microbiota in the face of nutritional deficiencies. and also provide a strong rational for understanding the roles of gut microbiota in the adaptation of QTP wildlife when facing harsh feeding environment.